(untitled) (Journal of Engineering, 2010)
Series compensation is frequently found on long transmission lines used to improve voltage stability. Due to the long transmission lines, voltage begins to decay as the line moves further from the source. Series compensation devices placed strategically on the line to increase the voltage profile of the line to levels near 1.0 p.u.. This paper presents a novel optimum location and optimum percentage compensation value of a series capacitor as a compensation method to enhance the voltage stability and loss reduction. The proposed method is applied to a 11-bus power system.The load flow analysis using Newton-Raphson approach for the 11-bus test system was designed and tested using MATLAB 7 programming language.